Technologically Enhanced Art Therapy: Introducing a New Synergistic Model to Enhance Morphological Awareness in Students with Dysgraphia - Rabih Nabhan; Nouhad Kamel (Britain International for Academic Research (BIAR-Publisher), 2021)
Writing is an essential task for self-expression. While it is normal for otherwise healthy students to struggle with handwriting, for a small group of students with a transcription learning disability (LD) called dysgraphia, rather than improving the learning process, writing creates a major hurdle that interferes with learning. Because most of their energy is spent on the process of writing, students with dysgraphia risk falling behind at school. More importantly, they are vulnerable to cumulative emotional and behavioral problems which are often left unattended. Art therapy and technology have been incorporated in a variety of ways into treatment of LDs. In the current study, a new hybrid model that builds on earlier empirical research is prosed to provide a compensatory strategy to assist students with dysgraphia. The concurrent treatment approach incorporates drawing activities with the use of mobile devices (specifically the application WhatsApp) to facilitate the self-expression of students with dysgraphia, restore their self-confidence and enhance their skills to a level commensurate with their aptitude while attending to their psychological well-being. Furthermore, the suggested trifold plan is intended to help students with dysgraphia by directly targeting their morphological awareness. The ultimate goal of the interactive strategy is to improve the environment in which students with dysgraphia are learning so that they can focus on their creativity and feel less excluded in normal classrooms. Further empirical research on concurrent dysgraphia treatments is warranted.